2014
DOI: 10.1039/c4dt02162b
|View full text |Cite
|
Sign up to set email alerts
|

Structural limitations for optimizing garnet-type solid electrolytes: a perspective

Abstract: Lithium ion batteries exhibit the highest energy densities of all battery types and are therefore an important technology for energy storage in every day life. Today's commercially available batteries employ organic polymer lithium conducting electrolytes, leading to multiple challenges and safety issues such as poor chemical stability, leakage and flammability. The next generation lithium ion batteries, namely all solid-state batteries, can overcome these limitations through employing a ceramic Li + conductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 83 publications
3
43
0
Order By: Relevance
“…S5). Ions are concentrated in the neighboring pores of the commercial PP separator due to the inert Li-ion conductivity of the PP separator ( 31 ). The pores in PP filled with liquid electrolytes are the only pathway for Li-ion migration.…”
Section: Resultsmentioning
confidence: 99%
“…S5). Ions are concentrated in the neighboring pores of the commercial PP separator due to the inert Li-ion conductivity of the PP separator ( 31 ). The pores in PP filled with liquid electrolytes are the only pathway for Li-ion migration.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research along these lines has shown that certain Li-oxide garnets have the necessary high ionic conductivities, as well as chemical and physical properties, to be considered as potential electrolytes in solid-state batteries (e.g. reviews of Cussen, 2010;Ramzy & Thangadurai, 2010;Zeier, 2014;Thangadurai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The areal specific resistance (ASR) is investigated by ab initio calculations in this article, to predict the intrinsic ASR as lower limitation. Among the existing SEs including Li 3 N, [3] Na superionic conductor (NASICON), [4] perovskite, garnet, thio-Îł -Li 3 PO 4 related system [5] (including glass and glass-ceramic states), thio-Li superionic conductor (LISICON), [6] and Li 10 GeP 2 S 12 , [7] garnet structured Li ionic conductors attract dominated interests in recent years [8,9] mainly owing to an absence of valence variant elements and a resulting higher electrochemical stability especially with Li metal anode. The first step is investigated by climbing image nudged elastic band (CI-NEB), resulting in barrier energy lower than 0.37 eV compared to experimental 0.34 eV of the garnet bulk phase.…”
mentioning
confidence: 99%
“…As the flammable organic liquid electrolyte is the main case of the urgent safety problem, the solid electrolytes (SEs) without flammable organic small molecular liquid gradually attracts wide attention, including inorganic ceramic electrolytes and dry organic polymer electrolytes. Among the existing SEs including Li 3 N, [3] Na superionic conductor (NASICON), [4] perovskite, garnet, thio-Îł -Li 3 PO 4 related system [5] (including glass and glass-ceramic states), thio-Li superionic conductor (LISICON), [6] and Li 10 GeP 2 S 12 , [7] garnet structured Li ionic conductors attract dominated interests in recent years [8,9] mainly owing to an absence of valence variant elements and a resulting higher electrochemical stability especially with Li metal anode. However, the lithium metal anode shows poor compatibility with traditional organic liquid electrolyte owing to a continuously evolving Li/electrolyte interface during charge/discharge.…”
mentioning
confidence: 99%
See 1 more Smart Citation